Bernstein revisited: the recontextualisation of equity in contemporary Australian school education. Issue 2 (17th February 2016) - Loughland, Tony; Sriprakash, Arathi
Abstract : This article draws on the sociology of Basil Bernstein to show how his detailed theories of 'recontextualisation' and the 'pedagogic device' provide useful analytic levers to examine the politics of educational change. We focus on recent policy developments that have significantly impacted Australian school education: the Program for International Student Assessment; the National Assessment Programme for Numeracy and Literacy; and the government's public dissemination of school achievement data through the MySchool website. The analysis illustrates the ways in which the logics of economic rationalism not only have become ubiquitous in Australian education policy, but have come to recontextualise – or reshape – discourses of social and educational equity through new norms of competition, standardisation and commensurability. In doing so, the paper highlights the value of a Bernsteinian approach to understanding the vernacular character of neoliberalism in contemporary educational policy.